Commercialization of accounting profession: the case of non-audit services - Muhamad Sori, Zulkarnain; Karbhari, Yusuf; Ramadilli Mohd, Shamsher Mohamad (Faculty of Economics and Management, Universiti Putra Malaysia, 2010)
Over the last decade, the accounting profession has witnessed the commercialisation of audit firms through offering of non-audit services (i.e. business consultancy services) to their audit client. Regulators and stakeholders have placed a great concern on the potential threat of commercialization of audit services on perceived auditor independence. This study reports the effects of the joint provision of audit and non-audit services (NAS) and the type of NAS on perceived auditor independence. The main findings suggest that auditor independence is perceived to be compromised when audit and NAS were jointly offered by audit firms. However, when there exist proper segregation of duties in audit firms that offer both services, the perception changed.